2008
DOI: 10.1002/cncr.23493
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in extremity soft tissue sarcoma after a pathologically negative re‐resection and without radiotherapy

Abstract: BACKGROUND.The purpose was to define the rate of local recurrence (LR) and identify prognostic factors for LR in patients with extremity soft‐tissue sarcoma (STS) treated with limb‐sparing surgery and a pathologically negative re‐resection specimen without radiotherapy (RT).METHODS.A review of the prospective sarcoma database identified 200 patients with primary, nonmetastatic, extremity STS treated with limb‐sparing surgery between June 1982 and December 2002 who had a pathologically confirmed negative re‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Old age and stage 3 disease were identified as factors associated with a higher rate of local recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…Old age and stage 3 disease were identified as factors associated with a higher rate of local recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective analyses in adults with soft tissue sarcomas indicate that adjuvant radiotherapy is not necessary for patients whose tumour can be adequately excised, even when the tumour is high grade or >5 cm in maximal diameter [14,15,21]. An analysis of paediatric SS patients treated on three prospective European studies showed that a significant proportion could be cured without radiotherapy when a strategy of omitting radiotherapy for those with a complete response to surgery and chemotherapy was utilized [5].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies identified a group of low-risk SS cases to be treated with surgery alone. This treatment strategy was based on retrospective analyses suggesting that adjuvant chemotherapy and radiotherapy might be omitted in low-risk SS [1315], but no prospective series have confirmed the safety of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…In the 12 patients undergoing a wide local excision achieving clear surgical margins, six had tumor less than 5.0 cm in the greatest dimension. Based on retrospective data in adults, this group of pediatric patients who have undergone a wide resection may be candidates for observation alone in the context of a clinical trial (as is being done in Children’s Oncology Group trial ARST0332) (2730). Patients with primary disease involving the trunk or head and neck did not experience an adverse local outcome despite the historic adverse prognosis that these features would predict (24, 25).…”
Section: Discussionmentioning
confidence: 99%